Kurdish folklore source of pain women's cries for example - Sabir, Bawar Nuruddin (Sulaimani Journal for Humanities, 2026)
In the first part, I have given a quick look at the history of Kurdish society and briefly mentioned three factors that have had a negative impact on society and as a result have placed the greatest burden on women's lives. In the second part, I have discussed the situation of women in Kurdish society and tried to answer the following questions: What is culture? Are the current traditions in Kurdish culture part of the ancient culture of Kurdish society and have existed since ancient times? How have the powers of the ruling nations over the Kurds worked to distort Kurdish culture? Have women had a place in Kurdish culture? In the third part, I have presented some examples of women's cries in Kurdish folklore, which answer some questions, such as: What was the position of women in Kurdish culture? Have women been silent in the face of violence? What has been women's resistance to all these traditions that have used women as tools?